(untitled) (Desenvolvimento em Questão, 2026)
The main objective of this paper is to investigate empirically the explain factors of the Brazilian Maternal Mortality. Actually the Brazilian maternal mortality rate is stagnant and shows no signs of falling. After identifying the national and international literature in the area of ​​Economics and Health, it can be seen that maternal mortality is analyzed from the point of view of the stage of development, where a country that develops reduces maternal deaths. For this, there are specific public policies aimed at pregnant women and children. In Economics, the explanation of maternal mortality is a result of the analysis of infant mortality: one must invest in education (proxies of human capital) to reduce mortality. The contribution of this article lies in the definition of an econometric model, through logistic regression, with data from the Mortality Information System (SIM - DATASUS) between 1996 and 2019, which considers the individual and verifies as true the hypothesis of Economy on the drop in maternal mortality with increased schooling. There is also a situation of inequality among Afro-descendant women, who are more likely to die than white women.